2015
DOI: 10.1038/npjschz.2015.16
|View full text |Cite|
|
Sign up to set email alerts
|

Voxel-based, brain-wide association study of aberrant functional connectivity in schizophrenia implicates thalamocortical circuitry

Abstract: Background:Wernicke’s concept of ‘sejunction’ or aberrant associations among specialized brain regions is one of the earliest hypotheses attempting to explain the myriad of symptoms in psychotic disorders. Unbiased data mining of all possible brain-wide connections in large data sets is an essential first step in localizing these aberrant circuits.Methods:We analyzed functional connectivity using the largest resting-state neuroimaging data set reported to date in the schizophrenia literature (415 patients vs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
120
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(134 citation statements)
references
References 41 publications
12
120
2
Order By: Relevance
“…The thalamus is connected to all cortical areas and conveys information to the neocortex, including information from the basal ganglia. Though a number of other studies have identified thalamic connectivity changes in the chronic stage of schizophrenia, 17,19,[22][23][24] such studies provide little information about early illness pathophysiology. In contrast, studies of FE schizophrenia have the advantage to specify brain changes at illness onset, thus providing crucial information about the pathogenesis of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The thalamus is connected to all cortical areas and conveys information to the neocortex, including information from the basal ganglia. Though a number of other studies have identified thalamic connectivity changes in the chronic stage of schizophrenia, 17,19,[22][23][24] such studies provide little information about early illness pathophysiology. In contrast, studies of FE schizophrenia have the advantage to specify brain changes at illness onset, thus providing crucial information about the pathogenesis of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] Despite numerous leads, the reported findings are somewhat inconsistent and the core regions associated with the pathogenesis of schizophrenia still remain controversial.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, full-brain studies will be required to get a more comprehensive view on AD-related changes in rsfMRI network connectivity using meta-analyses. The current trend toward large public samples [13,62] is enabling unbiased metaanalyses, pooling neuroimaging data across many studies instead of relying on published coordinates. This will hopefully resolve most of the aforementioned limitations in the future.…”
Section: Limitationsmentioning
confidence: 99%
“…However, the use of different parcellation schemes could lead to substantially different network structure and statistics [6,9], and there is no consensus on the ideal parcellation resolution, which is a compromise between spatial variability of the functional signals and anatomical interpretability [6,10]. Despite this, due to computational limitations only few studies have explored FC at the voxel resolution with direct assessment of the FC matrix [11][12][13][14][15][16][17]. Others [18,19] circumvented the problem by investigating eigenvector centrality of functional networks, with a fast computation method introduced by [20] that avoids the explicit calculation of the FC matrix.…”
Section: Introductionmentioning
confidence: 99%